Bimodal Presentation Speeds up Auditory Processing and Slows Down Visual Processing - Robinson, Christopher W.; Moore, Robert L.; Crook, Thomas A. (Frontiers in Psychology, 2018)
Many situations require the simultaneous processing of auditory and visual information, however, stimuli presented to one sensory modality can sometimes interfere with processing in a second sensory modality (i.e., modality dominance). The current study further investigated modality dominance by examining how task demands and bimodal presentation affect speeded auditory and visual discriminations. Participants in the current study had to quickly determine if two words, two pictures, or two word-picture pairings were the same or different, and we manipulated task demands across three different conditions. In an immediate recognition task, there was only one second between the two stimuli/stimulus pairs and auditory dominance was found. Compared to the respective unimodal baselines, pairing pictures and words together slowed down visual responses and sped up auditory responses. Increasing the interstimulus interval to four seconds and blocking verbal rehearsal weakened auditory dominance effects, however, conflicting and redundant visual cues sped up auditory discriminations. Thus, simultaneously presenting pictures and words had different effects on auditory and visual processing, with bimodal presentation slowing down visual processing and speeding up auditory processing. These findings are consistent with a proposed mechanism underlying auditory dominance, which posits that auditory stimuli automatically grab attention and attenuate/delay visual processing.